Relationship between Pressure Ulcers in Elderly People and Physiological Indices of the Skin - Kohara, Hiroko Takeshima; Ikeda, Mitsunori; Okawa, Masami (Acta medica Okayama, 2021)
This study examined the relationship between skin physiological indices and pressure ulcers in elderly people. The subjects were 55 bedridden elderly Japanese patients with a median age of 85 years. The following parame-ters were measured using non-invasive devices: skin surface temperature, moisture content in the stratum corneum, moisture content in the dermis, transepidermal water loss as an index of skin barrier function, skin erythema and skin elasticity. The sacral and 2 heel areas were observed as sites predisposed to pressure ulcers. Within one month after measuring the skin physiological indices, we confirmed pressure ulcers of National Pressure Ulcer Advisory Panel classification Stage II or worse based on medical records. Among the 55 patients, 4 (7.3%) prospectively developed a total of 5 pressure ulcers within 16 days. Only the skin erythema score was significantly higher with than without pressure ulcers (p < 0.001). We performed a binary logistic regression analysis and confirmed a significant relationship between pressure-ulcer development and the level of erythema (odds ratio = 1.026; 95% confidence interval: 1.011-1.042). Skin erythema increased before the development of pressure ulcers. Taken together, our results show that the high skin erythema score can be a predictive indicator of pressure ulcers.